Factors Affecting life Satisfaction of Employees under Financial Threat - Dr. Rizwan Qaisar Danish; Rabia Shahid; Hafiz Fawad Ali (SEISENSE Journal of Management, 2019)
Purpose- Life satisfaction is a level in which feelings of people are affected positively or negatively about their lives. Employees whose lives are more satisfied are generally more committed with their works, reveal low absenteeism and more efficient in doing duties. This study aims to investigate what factors affect life satisfaction of employees in the banking sector specifically in the Pakistani context. Design/Methodology- The target population of this study was non-managerial employees of banks in Lahore. Total 340 questionnaires were distributed among employees in which 60 were filled incomplete and 30 were lost. The data were collected through self-administered questionnaires distributed to 250 respondents. Findings- The findings of structural equation modeling showed that economic hardship, prospective anxiety, and work stress has a negative impact on life satisfaction. Results also show that economic hardship and prospective anxiety has a positive impact on the financial threat. The financial threat is negatively related to life satisfaction. Practical Implications- It can also help managers to understand the insight of employee adverse financial decision making. Managers also make guidelines which may minimize all the consequences of psychological distress. It also helps in identifying methods to reduce anxiety, stress and economic hardship.